CPU Burst Processes Prioritization Using Priority Dynamic Quantum Time Algorithm: A Comparison with Varying Time Quantum and Round Robin Algorithms - Mohammed, Maysoon A.; Mazlina, Abdul Majid; Balsam, A. Mustafa; Ghani, Rana Fareed (The International Journals of Engineering and Sciences (IJENS), 2015)
In Round-Robin Scheduling, the time quantum is fixed and processes are scheduled such that no process uses CPU time more than one time quantum in one go. If time quantum is too large, the response time of the processes will not be tolerated in an interactive environment. If the time quantum is too small, unnecessary frequent context switch may occur. Consequently, overheads result in fewer throughputs. Round Robin scheduling algorithm is the most suitable choice for time shared system but not for soft real time systems due to a large turnaround time, large waiting time and high number of context switches. The choice of the quantum time in RR is the optimal solution for the problem of large turnaround and waiting time with RR. In this study, we propose a priority algorithm with dynamic quantum time (PDQT), to improve the work of RR by improving the concept of Improved Round Robin with varying time quantum (IRRVQ). The proposed algorithm gave results better than RR and IRRVQ in terms of minimizing the number of context switches, average waiting time, average turnaround time, design and analysis. The simple Round-Robin algorithm has been improved by about 40%. By controlling quantum time according to the priorities and burst times of the processes, we experience fewer context switches and shorter waiting and turnaround times, thereby obtaining higher throughput